1996
DOI: 10.1111/j.1476-5381.1996.tb16044.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of calcitonin gene‐related peptide on tracheal smooth muscle of guinea‐pigs in vitro

Abstract: 1 The effect of calcitonin gene-related peptide (CGRP) on airway smooth muscle is controversial. The aim of this study was to determine whether the action of CGRP on tracheal strips of guinea-pigs is modulated by epithelium and whether this peptide-induced action involves other mediators including nitric oxide (NO) and endothelin (ET)-1.2 CGRP produced a weak dose-dependent increase in guinea-pig tracheal tension in vitro (-logEC50 = 8.5 ± 0.1, maximum contraction = 8.3 + 1.2% of 50 mM KCl-induced contraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Bradykinin, endothelin-1, substance P, adenosine, and calcitonin-gene related peptide, applied to the inside of intact tracheal tubes, provoke concentration-dependent relaxations (9,93,(101)(102)(103)316). The relaxations are reversed into contractions (or contractions are markedly potentiated) by NOS inhibitors, indicating that the relaxant effect in the airways is mediated by the release of endogenous NO (9,93,(101)(102)(103)316).…”
Section: In Vitro Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Bradykinin, endothelin-1, substance P, adenosine, and calcitonin-gene related peptide, applied to the inside of intact tracheal tubes, provoke concentration-dependent relaxations (9,93,(101)(102)(103)316). The relaxations are reversed into contractions (or contractions are markedly potentiated) by NOS inhibitors, indicating that the relaxant effect in the airways is mediated by the release of endogenous NO (9,93,(101)(102)(103)316).…”
Section: In Vitro Studiesmentioning
confidence: 91%
“…The relaxations are reversed into contractions (or contractions are markedly potentiated) by NOS inhibitors, indicating that the relaxant effect in the airways is mediated by the release of endogenous NO (9,93,(101)(102)(103)316). This effect was mimicked by removal of airway epithelium (111), suggesting that airway epithelium releases NO, which counteracts smooth muscle contraction induced by different spasmogens (9,93,(101)(102)(103)316). These striking results demonstrate the functional importance of epithelium in airway reactivity, not merely considered as a physical protective barrier between spasmogens and smooth muscle but as a modulator of bronchomotor tone via the release of relaxant substances (so-called epithelium-derived relaxing factors).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…[55][56][57] Intraluminal perfusion of tracheal tube preparations has shown that bradykinin, endothelin-1, substance P, adenosine, and calcitonin gene related peptide applied to the inside of intact tracheal tubes provoke concentration dependent relaxation. [58][59][60][61][62][63] The relaxation is reversed into contractions (or contractions are markedly potentiated) by NOS inhibitors, indicating that the relaxant effect in the airways is mediated by the release of endogenous NO. [58][59][60][61][62][63] This effect was mimicked by removal of airway epithelium, suggesting that airway epithelium releases NO which counteracts smooth muscle contraction induced by different spasmogens.…”
Section: No and Bronchoprotectionmentioning
confidence: 99%
“…For example, regardless of the origin of the airway preparation used (animal species and level of the tracheobronchial tree), most studies examining the effect of CGRP on the baseline tension of the airway smooth muscles resulted in identical data, as no contractile or relaxant response was observed (9, 10, 17-20, 23, 24, 26, 27, 29). In studies showing a contractile action for CGRP (for example, in guinea pig trachea), there is a consensus regarding the epithelium dependency for this effect of the peptide but the magnitude of the response evoked by CGRP was each time described as being weak and of minor importance: 30% of the maximum induced with 1.5 ϫ 10 Ϫ5 M of methacholine (20), 14% of the capsaicin (10 Ϫ5 M) maximum (21), and 8% of 50 mM KCl-induced contraction (31). Thus, when compared with SP and NKA, which Lung samples were collected in areas adjacent to the tissue preparations used for the bioassays.…”
Section: Discussionmentioning
confidence: 99%